2022
DOI: 10.1021/acsomega.2c01297
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Purity Calcium Carbonate by Mineral Carbonation Using Concrete Sludge

Abstract: A new type of mineral carbonation process for concrete sludge, a waste of fresh concrete under hydration, was developed, and the carbonation performances of the process were examined by laboratory-scale experiments. The process is composed of two steps; filtration of concrete sludge and bubbling of CO 2 into the filtrate to form calcium carbonate. Model concrete sludge, a mixture of cement and water, was filtered through a cellulose filter after hydration for 24 h to obtain a solution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, the use of organic insulation materials in underground spaces is restricted due to their high susceptibility to fire hazards. Inorganic insulation materials, particularly foam concrete materials, are gaining significant interest among researchers due to their noncombustibility and thermal insulation properties. A review of the literature indicates that foam concrete is predominantly prepared using mechanical foaming methods or chemical foaming techniques. , He et al produced alkali-activated slag foamed concrete with a dry density of 600–800 kg/m 3 using mechanical foaming, and it was observed that as the foam content increased, the thermal conductivity of the foamed concrete gradually decreased . However, the addition of preformed foam to concrete slurry through mechanical foaming results in compromised foam durability due to the mixing and pouring processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of organic insulation materials in underground spaces is restricted due to their high susceptibility to fire hazards. Inorganic insulation materials, particularly foam concrete materials, are gaining significant interest among researchers due to their noncombustibility and thermal insulation properties. A review of the literature indicates that foam concrete is predominantly prepared using mechanical foaming methods or chemical foaming techniques. , He et al produced alkali-activated slag foamed concrete with a dry density of 600–800 kg/m 3 using mechanical foaming, and it was observed that as the foam content increased, the thermal conductivity of the foamed concrete gradually decreased . However, the addition of preformed foam to concrete slurry through mechanical foaming results in compromised foam durability due to the mixing and pouring processes.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic insulation materials, particularly foam concrete materials, are gaining significant interest among researchers due to their noncombustibility and thermal insulation properties. 24 32 A review of the literature indicates that foam concrete is predominantly prepared using mechanical foaming methods 33 35 or chemical foaming techniques. 36 , 37 He et al produced alkali-activated slag foamed concrete with a dry density of 600–800 kg/m 3 using mechanical foaming, and it was observed that as the foam content increased, the thermal conductivity of the foamed concrete gradually decreased.…”
Section: Introductionmentioning
confidence: 99%